ANALISIS DAYA SAING USAHATANI KELAPA SAWIT RAKYAT DI KECAMATAN SUBAH KABUPATEN SAMBAS - JAWARI, JAWARI; MUANI, ANI; RADIAN, RADIAN (Jurnal Social Economic of Agriculture, 2017)
This study was aimed to analyze the competitiveness of farming palm oil (competitive and comparative advantage), Random Sampling method was used to select 88 respondens was determined purposive. The reason for choosing of Subah District because this area is largest palm oil producers and largest and oil palm planting area in the Sambas Regensy . The data used primary and secondary data. The Policy Analysis Matrix (PAM) method was used to analysis data. farming palm oil in Subah District has competitive and comparative excellence.Private propitability(PP) and Social propitability (SP)is positive value of,   Private Cost Rasio (PCR) 0,24, Domestic Resources Cost Ratio (DRCR) is 0,15. Transfer Output (TO) is value negatif Rp – 6.909.408,00/ha/year , it’s shows nothing transfer from consument to produsent, value 0,80 Nominal Protection Coefficient on Output (NPCO) or NPCO < 1,  output price not significant for farmers income.